FRI0571 A New Computer Based Tool for the Quantification of Radiographic Joint Damage in Rheumatoid Arthritis – Initial Results. (9th June 2015) - Langer, A.; Pfeil, A.; Renz, D.M.; Böttcher, J.; Langer, H.-E.
Abstract : Background: Radiographic progression is a key outcome parameter in rheumatoid Arthritis (RA) 1 . Manual scoring of joint damage based on the established scoring methods (e. g. Sharp Score) is a very time-consuming process with an average time of 30 minutes per image set 2 . Objectives: The objective of this initial feasibility study is to evaluate a new software tool for the computer based documentation of joint damage in RA. Methods: In a pilot study, 15 sets of X-rays of 15 patients with RA (12 female, 3 male; mean age 70.9±4.8 years) were read for bone erosions, joint space narrowing and bone mineralization in 82 areas (54 hand areas and 28 feet areas). The analysis of the X-rays was performed as a consensus-reading by two experienced readers. A computer based documentation system developed by the first author provides uniform templates of the hands and the feet, into which all identified erosions, joint space narrowing, (sub-)luxation and demineralization were transcribed with a stylus on a tablet (cf. Fig 1 ). The tool automatically computed the Ratingen score 3 and the Sharp/van der Heijde score 4 from the documented structural changes. Additionally, the time for the documentation in the computer was measured. Results: The mean time for the documentation of the structural changes in all areas was 16.0±6.2 minutes (range: 6-31 minutes; median time: 15 minutes) per image set. The scores were automatically computed as 17.9±14.1 points (range: 1 - 50 points; median: 13 points) for the Ratingen score, as 32.5±28.0 points (range: 2 – 97 points; median: 27 points) for the erosion score segment and as 54.7±27.0 points (range: 11 – 105 points; median: 52 points) for the joint space narrowing segment of the Sharp/van der Heijde score. Conclusions: The new tool allows for an easy and fast documentation. In this pilot study, the times to assess and document the structural changes on the hand and foot joints in patients with RA were significantly lower than those reported in the literature 2 . Multiple scores are computed automatically from the same source data by the system. These points might be of great potential and benefit for X-ray scoring over the time, especially in clinical and research settings. References: van der Heijde DM. Radiographic imaging: the 'gold standard' for assessment of disease progression in rheumatoid arthritis. Rheumatology (Oxford). 2000; 39: Suppl 1:9-16. Rau R, Wassenberg S. Bildgebende Verfahren in der Rheumatologie: Scoring-Methoden bei der rheumatoiden Arthritis.Z Rheumatol 2003; 62:555–565. Rau R, Wassenberg S, Herborn G, Stucki G, Gebler A. A new method of scoring radiographic change in rheumatoid arthritis. J Rheumatol 1998; 25:2094–2107. van der Heijde DMFM. Plain X-rays in rheumatoid arthritis: overview of scoring methods, their reliability and applicability. Bailliere's Clinical Rheumatology 1996; 10:435–453. Sharp JT, Young DY, Bluhm GB, Brook A, Brower AC et al. How many joints in the hands and wrists should be included in a score of radiologic abnormalities used to assess rheumatoid arthritis? Arthritis Rheum 1985; 28:1326–1335. Disclosure of Interest: None declared